The Assessment of Stiffness Modulus Characteristic of Asphalt Concrete With The Existing Moisture – A Review - Edmond, Samson; Shamshuddin, Mustafa Kamal (Recent Trends in Civil Engineering and Built Environment, 2021)
Moisture damage is one of the major problems that contribute to asphalt concrete (AC) distress due to the loss of stiffness modulus characteristic. The presence of moisture in AC had affected the strength of adhesive and cohesive properties of bitumen and mixture components. Due to these problems, the bond between AC mixture becomes weak and leads AC to manifest distress such as stripping, rutting, and raveling. This study was conducted by reviewing the previous research journal that related to this issue and the main objective is to evaluate the stiffness modulus characteristic of AC with and without moisture effect. Besides that, this study also evaluated the capability of additive in AC mixture to resist the effect of moisture. The comparison between stiffness modulus results from the Indirect Tensile Stiffness Modulus (ITSM) test for conditioned and unconditioned samples has been made. In order to categorize the most susceptible or resistant to moisture AC mixture, the Indirect Tensile Strength (ITS) and Tensile Strength Ratio (TSR) value has been identified. Based on the result of the comparison of ITS and TSR ratio, it showed that the use of additives in AC mixture indicated the improvement and relatively resistance to moisture. From ITSM test result, it shows that the stiffness modulus characteristic of AC mixture reduced with the presence of water. This result was similar with the AC mixture sample with additive. In order to approach a better understanding and improvement for the study, it is possible to recommend for future investigation, it should consider the reliability and repeatability of the test result. The assessment and evaluation of moisture damage resistance of AC mixture supposed to be in the range of the optimum value of additive that been mixed in the AC mixture. With the comprehensive assessment and analysis, it will provide guidance for the industry to produce stable, durable, and moisture resistance AC mixture.